The Impact of K-Pop Digital Marketing Communication Strategy on Indonesian Gen Z’s Dairy Purchase Intention Behavior - Supendi, Valencia Christina; Winarko, Hilarius Bambang (Universitas Muhammadiyah Surakarta, 2023)
This research aims to examine the influence of digital marketing communication strategies employed by Ultra Milk Make Your Move (Ultra Milk MYM), including celebrity endorsement and sales promotion, on the purchase intentions of Generation Z. The study addresses the context of the Indonesian dairy industry, where milk consumption remains relatively low compared to other countries. By exploring the marketing efforts of Ultra Milk MYM and its utilization of ITZY K-Pop musical group celebrity endorsers and promotional activities via digital platforms, this research seeks to shed light on their effectiveness in stimulating interest and driving purchase intentions among the younger generation. Drawing upon the theory of premiums and contests as effective promotional tools, this study investigates the impact of these strategies on brand perception and the generation of customer databases. The K-Pop celebrity endorser factor and the sales promotional strategy by using premiums and contests showed significantly influence the Gen Z to purchase the dairy product. The findings of this research provide valuable insights for both marketers and the dairy industry in enhancing milk consumption and catering to the needs and preferences of Generation Z in Indonesia by using the K-Pop popularity among them. These instructions give you basic guidelines for preparing papers for ICEISS 2023. Use the same font and size given in this template for each section. Abstract is in English covering the central issues of the study, the objectives, the methods/approaches and the results of the study.